SOCIO-ECONOMIC FACTORS AND ACCESS TO HEALTH CARE SERVICES IN NORTHERN CITY DIVISION, MBALE CITY. - KHALAYI AISHA (My University, 2024)
ABSTRACT The study concentrated on socio-economic factors and access to health care services in Northern City Division, Mbale City and it concentrated on the following research objectives: To identify socio-economic factors affecting access to health care services in Northern City Division, Mbale City, to examine the challenges affecting access to health care services in Northern City Division, Mbale City and to determine interventions for improving access to health care services in Northern City Division, Mbale City. The study used a cross sectional research design and it used both qualitative and quantitative research methodology where it considered a population of 100 respondents and a sample size of 8o respondents. Study findings revealed concluded that age is one of the factors affecting access to health care services in Northern City Division, findings also concluded that Choice of health care and access differs by age and people in similar age groups show similar patterns in their choices, that lack of insurance often contributes to lack of access to health which is a far reaching challenge, Findings revealed that Financial needs and insufficient coverage to pay medical bills lead to skipping of necessary care, that receiving some financial support from philanthropy can work as a strategy to improve health care access, that that affiliating with large healthcare systems in urban settings can help rural facilities improve on health care in rural communities, and lastly findings concluded that adopting of a diverse and inclusive hiring policy may provide many of the same services as physicians thus improving access to health care provision. The study recommended that: There should be more investments by different Governments in a number of strategies to reduce on socio economic factors affecting access to health care services in Northern City Division Mbale City and that there is need for the community and societies to begin being part of the group that try solve the challenges affecting access to health care provision.